Evaluation of type 2 diabetes care management in nine primary care practices before and after implementation of the Criteria of Good Disease Management of Diabetes established by the Swiss Society of Endocrinology and Diabetology (Swiss Medical Weekly, 2022)
AIMS OF THE STUDY: Little is known about the quality of diabetes management of patients with type 2 diabetes mellitus (T2DM) in Swiss primary care. Based on the recommendations of the National Council Quality Assurance Programme, an interprofessional working group of the Swiss Society of Endocrinology and Diabetology (SSED) established population-based national criteria for good disease management of T2DM in primary health care (the diabetes score). The objective of this study was to assess whether the implementation of these criteria improve diabetes management in primary care.METHODS: The diabetes score comprises eight criteria including three biometric measurements, two lifestyle-specific items and screening of three diabetes-associated complications. Practices can evaluate adherence to the criteria based on a point system, with the recommended aim to achieve ≥70/100 points. Group practices and single practices were included in this study and started implementing the SSED criteria in January 2018. The resulting score was compared with data retrospectively obtained for 2017. The primary endpoint was the overall change in Diabetes Score between 2017 and 2018 at each practice, further stratified by practice type. The absolute effect on individual diabetes score criteria was assessed by pooling all patient-level data.RESULTS: Nine practices (six single and three group) participated in the study. In 2017 and 2018, the primary care practices treated 727 and 704 patients with T2DM, respectively, of whom 676 were treated both years. Around half of the patients were cared for in group practices and half in single practices. Between 2017 and 2018 the median (interquartile range) diabetes score improved from 40 (35, 65) to 55 (45, 70; p = 0.078). One practice (single) obtained a score ≥70 in 2017, three practices (all single) achieved this target in 2018. Pooling patient-level data, we observed a significant absolute improvement in the following criteria: number of regular diabetes check ups, body mass index, glycated haemoglobin, blood pressure, low density lipoprotein cholesterol and screenings for diabetes-associated complications (all p